2008
DOI: 10.1016/j.pain.2007.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk markers for new onset irritable bowel syndrome – Results of a large prospective population-based study

Abstract: Irritable bowel syndrome (IBS) affects up to 22% of the general population. Its aetiology remains unclear. Previously reported cross-sectional associations with psychological distress and depression are not fully understood. We hypothesised that psychosocial factors, particularly those associated with somatisation, would act as risk markers for the onset of IBS. We conducted a community-based prospective study of subjects, aged 25–65 years, randomly selected from the registers of three primary care practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 32 publications
11
97
0
Order By: Relevance
“…high illness behavior scores, anxiety, sleep problems and somatic symptoms) were six times more likely to develop IBS five months later when compared to those who were exposed to none or only one marker. Among these markers, the illness behavior scale was the stronger predictor of outcome (OR = 5.2, 95%CI 2.5-11.0) [9]. Similar results were reported by a recent study that included 2769 subjects from a screening program, among which 258 had IBS.…”
Section: Somatization and Ibssupporting
confidence: 86%
See 1 more Smart Citation
“…high illness behavior scores, anxiety, sleep problems and somatic symptoms) were six times more likely to develop IBS five months later when compared to those who were exposed to none or only one marker. Among these markers, the illness behavior scale was the stronger predictor of outcome (OR = 5.2, 95%CI 2.5-11.0) [9]. Similar results were reported by a recent study that included 2769 subjects from a screening program, among which 258 had IBS.…”
Section: Somatization and Ibssupporting
confidence: 86%
“…Somatization explains the frequent extra gastrointestinal (GI) symptoms reported by IBS patients: musculoskeletal complaints, urinary and sexual symptoms, headaches and fatigue [8]. Several papers have shown that psychosocial factors indicative of somatization (such as illness behaviour scores, anxiety, sleep problems and somatic symptoms) and somatization are independent risk factors for IBS [7,9,10]. In a large community based study from England, subjects free of IBS that reported all markers of somatization at baseline (i.e.…”
Section: Somatization and Ibsmentioning
confidence: 99%
“…Several studies have examined risk factors for PI-IBS [21,[28][29][30][31][32][33][34]. As found previously, risk of IBS was higher in females and younger age groups, although this was not significant.…”
Section: Discussionmentioning
confidence: 67%
“…Severity of GE (duration of diarrhoea, presence of blood in stools, abdominal cramps, weight loss), younger age and female gender have been associated with increased risk of PI-IBS [21,[28][29][30][31][32][33][34]. Anxiety, depression and major life events have also been identified as potential risk factors with some hypothesizing that these disorders prolong gut inflammation and heighten sensory perception [22,26,28,29,32,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of IBS in the general population is estimated to be around 10-20% [1,4]. Depending on the predominant symptoms, 3 types of IBS can be distinguished: IBS with constipation, with diarrhea, or with alternating constipation and diarrhea.…”
mentioning
confidence: 99%